A TRIBUTE TO AL-MARHUM PROFESSOR DATUK MOHAMED MACKEEN (1928–2013) - Hassan, Mohd. Kamal (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
Professor Mackeen, together with the late Tan Sri Dr. Abdul Rauf, laid the foundation of Islamic Religious Studies in the then newly established Department of Islamic Studies, University of Malaya, in 1961. The department offered courses on Islamic thought, law, mysticism, history, literature, Qur’anic exegeses and Arabic language. I joined the department as an undergraduate student in1963 when the late Tan Sri Dr. Abdul Rauf was the head. A few years later Tan Sri left Malaysia to work in the U.S.A. and Professor Mackeen took over as the head for several years.